ANALISIS PENGARUH STRUKTUR MODAL, KEPEMILIKAN SAHAM MANAJEMEN, PROFITABILITAS, UKURAN PERUSAHAAN, DAN LIKUIDITAS, TERHADAP KEBIJAKAN DIVIDEN DALAM MENINGKATKAN NILAI PERUSAHAAN - Irmawati, Dessy (JURNAL BISNIS STRATEGI, 2012)
The purpose of this study is analyzing the impact of the variable Debt to Equity Ratio (DER), Insider Ownership (IO), Return On Asset (ROA),  Firm Size (SIZE), Current Ratio (CR), on variable Deviden Payout Ratio (DPR) and corporate value on manufacturing companies  listed in Indonesia Stock Exchange 2008 – 2011 period. Research using purposive sampling method for taking samples with the following criteria: (1) manufacturing company published financial report during period 2008 -2011; and (2) manufacturing company which always pays deviden within period of research (2008-2011). The Data was based on publicity Indonesian Capital Market Directory (ICMD) from 2008 to 2011. Sample was acquired 134 observed. Data was analyzed with multi linier regression of ordinary least square and hypotheses was tested using t-statistic and f-statistic at level of significance 1%, 5%, 10%. Analysis result shows that insider ownership, ROA is partially affecting DPR have a significance value less than 5%, while firm size, liquidity and current ratio are not significant impact on DPR. ROA, DPR and firm size able to affect company value have a significance value less than 5%, while DER,insider ownership,  liquidity and current ratio are not significant impact on company value. The implication is that the company should prioritize ROA since ROA is a variable which dominantly affecting DPR and company value. The meaning of strategy which is done through investment strategy that is based on ROA has positif relationship upon deviden policy which means if the company has high profitability will give increase of deviden policy actually increase company value.